Sistem Informasi Pendataan Pemohon Sertifikat Tanah di BPN Kabupaten Nabire Menggunakan Metode RAD - Kristia Yuliawan; Mei Herba; Arief Rahman Hakim (Jurnal Teknologi dan Informatika, 2024)
The management and data collection of land certificates requires a sophisticated and efficient technological approach to ensure the smooth running of administrative processes at the Nabire National Land Agency (BPN). This article discusses the implementation of the Land Certificate Applicant Data Collection Information System using the Rapid Application Development (RAD) Method. The RAD method is used to deal with rapidly changing needs and supports system development in a short time. The results showed that the use of RAD successfully improved the efficiency of the data collection process, provided a solution that was responsive to stakeholder needs, and produced a high quality final product. The active involvement of stakeholders, including BPN officers and applicants, was key to the successful implementation. Despite the success, this study recommends regular updates using the RAD method, continued training for users, and the implementation of stronger security features to maintain the availability and relevance of the system. This abstract provides a brief overview of how RAD implementation can bring positive changes in the land certificate applicant data collection system at BPN Nabire, opening up opportunities for further development and increased efficiency.